PENGARUH BUDAYA KERJA, LINGKUNGAN KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA PR ALAINA FAJAR BERLIAN TULUNGAGUNG - Ekasari, Virga Dyah; Leksono, Anwar Bowo; Jatmiko, Udik (Commodities, Journal of Economic and Business, 2023)
The development of technological advances and the increasingly high rate of economic growth, increasing the number of companies in the industrial branch, currently a lot of cigarette businesses are developing very rapidly, marked by competition in the business world. Problems often occur when the attitude and behavior of employees decreases so that it affects the level of productivity of work skills. This problem was felt by PR employee Alaina Fajar Berlian Tulungagung. The research objective was to determine the significant effect of work culture, work environment and work stress on employee productivity partially or simultaneously. The population in the study was taken from several production employees. Methods of analysis using quantitative inferential statistics include validity, reliability, assumption test, multiple linear regression, hypothesis testing. The results showed that the work culture variable partially had a positive and significant effect on employee work productivity with a significant t 0.001 <0.05 meaning Ha1 was accepted. The work environment variable partially has a positive and significant effect on employee work productivity with a significant t 0.000 <0.05 meaning Ha2 is accepted. Work stress variable partially has a positive and significant effect on employee work productivity with a significant t 0.001 <0.05, which means Ha3 is accepted. The variables of work culture, work environment and work stress simultaneously have a positive and significant effect on employee work productivity with a significant F of 0.000 <0.05 meaning Ha3 is accepted.